Glacier systems and seasonal snow cover in six major Asian river basins: hydrological role under changing climate - Savoskul, Oxana S.; Smakhtin, Vladimir U. (International Water Management Institute, 2013)
The hydrological roles of glaciers and seasonal snow in the Indus, Ganges, Brahmaputra, Amu Darya, Syr Darya and Mekong basins are, for the first time, assessed comprehensively at a major river basin scale in this paper. Contribution of glacier runoff, subdivided into renewable and nonrenewable components, and seasonal snowmelt to mean annual flow is evaluated for two time slices: 1961-1990 and 2001-2010. The recent changes of the hydrological roles of glaciers and snow, and the most likely changes of those under future climate change are analyzed.